Kebijakan Pendidikan Di Indonesia : Analisis Tantangan Dan Peluang Dalam Implementasi Di Lapangan - Flora Putrian Adel; Eli Sabrifha (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Education policy in Indonesia is formulated as a strategic effort to improve the quality, relevance, and equitable distribution of educational services across various regions. However, the implementation of these policies at the school level still faces a range of complex challenges. This study aims to analyze both the challenges and opportunities in implementing aducation policies in Indonesia. The method used is a qualitative approach through a literature riview, examing various sources such as academic journals, book, and official policy documents. The findings indicate that the main challenges include limited educational facilities and infrastructure, disparaties in the quality of trenching persobbel, differences in geographical conditions across regions, and suboptimal coordination among relevant stakeholders. In addition, relatively rapit policy changes also demand a high level of adaptability from educational institutions. On the other hand, there are opportunities that can be leveraged, such as the development of digital technology that supports innovative learning, inscreasing increasing government attention to educational reform, and active community participation in supporting the educational process. Therefore, sustained collaboration among the government, educators, and the community is needed, along with strengthening the capacity of educational institutions, so that policy implementation can be more effective, responsive, and equitable.